Isolation, Identification and Leavening Ability of Yeast from Local Fruits (Asian Journal of Plant Biology, 2023)
Yeast is the organism used in the leavening of dough in a bakery. The study was carried out to determine the leavening ability of yeast isolated from different fruits. Three different yeast species were isolated from different fruits and were identified using cultural and microscopic methods. The yeast species isolated were tested for their temperature tolerance, ethanol tolerance, carbohydrate fermentation and leavening ability. The isolates were able to tolerate different temperature ranges (25 °C, 30 °C and 37 °C), and different concentrations of alcohols (2%, 4%, 6%, and 8%). They were also able to grow and ferment glucose, sucrose, and fructose. The ability of the identified yeast species to increase the volume of the dough was examined by fermenting flour dough. The fermentation was conducted at 30 °C for 72 h. Yeast isolates from date, pineapple, mango and commercial beakers yeast were found to have a leavening ability of 66, 60, 40 and 58, respectively, and the control having 20 cm3/g. This indicates that the fruits could be a potential source of indigenous yeast species which can serve as good leavening agents.
Keywords: Yeast; Local fruits; Isolation; Fermentation; Flour dough